Implementation of Audio-Visual Assisted Problem-Based Learning (PBL) Model to Improve Critical Thinking Skills - Andi Mustika; Nurul Fitriah Aras; Sinta Satria Dewi Pendit; Azizah Azizah; Khairunnisa Khairunnisa (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
This study aims to improve the Critical Thinking Skills of Grade IV Students of SDN 2 Talise through Classroom Action Research (CAR). CAR is a research method deliberately conducted in classroom settings to enhance learning quality. The research follows Kemmis and McTaggart's model, comprising four stages: Planning, Action, Observation, and Reflection. Conducted at SDN 2 Talise during the 2024/2025 academic year, this study involved 17 grade IV students as research subjects. Data collection employed both non-test and test techniques. Non-test methods included interviews, observations, and documentation, while test data was gathered through essay assessments evaluating students' critical thinking skills in social studies material. The study implemented Problem-Based Learning (PBL) assisted by audio-visual media. Results demonstrated progressive improvement across cycles. In Pre-Action, classical learning completion achieved 25%. Cycle I showed improvement to 30.76%, representing a 5.76% increase. Most significantly, Cycle II demonstrated substantial progress with 89.41% classical learning completion, indicating a remarkable 58.65% improvement from Cycle I. These findings reveal that PBL implementation with audio-visual support effectively enhances students' critical thinking abilities. The dramatic improvement from 25% to 89.41% completion rates across the research cycles demonstrates the model's effectiveness. The progressive enhancement pattern confirms that structured problem-based approaches, when properly implemented with multimedia support, can significantly develop elementary students' critical thinking skills in social studies education. Therefore, the Problem-Based Learning model proves successful in improving Grade IV students' critical thinking skills at SDN 2 Talise.